Utility and cost of low‐vacuum reinfusion drains in patients undergoing surgery for subcapital hip fracture repair. A before and after cohort study. Issue 1 (22nd July 2013) - Muñoz, M.; Iglesias, D.; Garcia‐Erce, J. A.; Cuenca, J.; Herrera, A.; Martin‐Montañez, E.; Pavia, J.
<x xml:space="preserve">Abstract</x> Background Postoperative blood loss may be a risk factor for allogeneic blood transfusion (ABT) in patients undergoing subcapital hip fracture (SHF) repair. We investigated the utility and costs of using a low‐vacuum reinfusion drain (Bellovac ABT) within a blood management protocol for reducing ABT requirements in consecutive SHF. Methods The blood management protocol consisted of the application of a restrictive transfusion trigger (Hb < 8 g/dl), the peri‐operative administration of IV iron sucrose (3 × 200 mg/48 h) ± recombinant erythropoietin (1 × 40 000 IU sc) and the use of Bellovac ABT (Group 2, n = 117). An immediate previous SHF series managed without Bellovac ABT served as control (Group 1, n = 138). Results Overall, 72 out of 255 (28%) received at least one ABT unit (2·1 ± 1·0 U/transfused patient) without differences between groups. However, in the subgroup of patients with admission Hb < 13 g/dl, the use of Bellovac ABT reduced postoperative ABT rates (16% vs. 46%, for groups 2 and 1, respectively; P = 0·001), although only 3 were reinfused, and was cost‐saving. The use of Bellovac ABT also resulted in fewer wound bleeding complications, but there were no differences in Hb at postoperative days 7 and 30 between groups. Conclusions In SHF patients with admission Hb < 13 g/dl and managed with peri‐operative IV iron ± recombinant erythropoietin plus restrictive transfusion indication, the use of Bellovac ABT was associated with reduced ABT requirements, without increasing postoperative complications, and cost‐savings.